2012
DOI: 10.1021/jp304817u
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Nonlinear Absorption of 5,10-A2B2Porphyrins in the Nanosecond Regime

Abstract: The nonlinear absorption (NLA) properties of free base and metalated porphyrins with a unique 5,10-A(2)B(2) substitution pattern were studied with open Z-scan technique at 532 nm in the nanosecond regime over a broad range of input fluence. The NLA responses were found to be dependent on structural features and the solvent used. In most cases, the character of the response differed from that typically observed for other porphyrins under similar experimental conditions (i.e., reverse saturable absorption, RSA),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…As demonstrated previously, the population of the state cannot be neglected and the 35 population buil-up of the unabsorptive state leads to an RSA/SA switch. 11 increases with increasing for the four-level model (Fig. 8 H,K).…”
Section: Impact Of the Four-level Model Fitting Parameters On The Nonmentioning
confidence: 83%
See 4 more Smart Citations
“…As demonstrated previously, the population of the state cannot be neglected and the 35 population buil-up of the unabsorptive state leads to an RSA/SA switch. 11 increases with increasing for the four-level model (Fig. 8 H,K).…”
Section: Impact Of the Four-level Model Fitting Parameters On The Nonmentioning
confidence: 83%
“…14,16,17 The remaining data for studies in DMF and toluene can be found in the previous publications. 11,12 The following trend in the solvent effect on could be 40 observed for most compounds: (DMF) < (toluene) ( respectively. The impact of these parameters on the NLA responses was studied.…”
Section: Solvent Effect On the Nonlinear Absorptionmentioning
confidence: 89%
See 3 more Smart Citations